The Influence of Age, Sex and Season on Andean Condor Ranging Behavior during the Immature Stage - Guido, Jorgelina María (2023)
Immature individuals move from their natal area to the area where they settle and reproduce, and this may take several years. This process is essential for long-lived species such as vultures and condors, which spend long periods as immature and move extensively. We studied the movement behavior of 26 GPS-tagged immature Andean condors (Vultur gryphus) from northwestern Patagonia throughout the immature stage, analyzing whether these patterns differed according to age, sex and season. We found that season and age influenced home range size and flight distances, the warm season being when immature condors move most; movement patterns were greater in sub-adults than in juveniles. The age effect was associated with the sex of individuals, with males increasing their home range more than females. Our results provide the first description of how immature Andean condor movement patterns are affected by internal and external factors. This information could be key to understanding condor responses to environmental change and threats at different stages during their immature phase. Until now, condor conservation efforts have not considered the areas used by dispersing individuals. Our results increase our understanding of ranging behavior during the immature stage of this threatened bird, enabling us to improve the conservation policies and management strategies designed to protect them.